Cellular adaptations of the scleractinian coral Madracis pharensis to chronic oil pollution in a Mediterranean shipwreck - Nardi, Alessandro; Resaikos, Vasilis; Papatheodoulou, Magdalene; Di Carlo, Marta; Vedhanarayanan, Harini; Regoli, Francesco; Gorbi, Stefania; Jimenez, Carlos (Frontiers in Marine Science, 2024)
Chemical pollution in marine ecosystems is a factor of stress interacting in multiple and complex ways with other major causes of deterioration, such as warming seas due to climate change. Here we surveyed epibenthic communities from a shipwreck in the Levantine Basin for temporal and spatial changes in the community in relation to chronic oil pollution, comparing results collected from an area of the wreck characterized by chronic oil leakage with another area not affected by oil. Polycyclic aromatic hydrocarbons (PAHs) bioaccumulation analyses were integrated with characterization of the efficiency of xenobiotics biotransformation processes and antioxidant network of the scleractinian coral Madracis pharensis, chosen as bioindicator species. Results highlighted the two areas hosting different epibenthic communities over a period of 11 years. Significant changes in the percentage cover of M. pharensis could be the result of recent mass mortality associated to Marine Heat Waves. Biological investigation conducted in M. pharensis tissues revealed an increased content of PAHs in specimens collected from the oil-impacted area, coupled with an increased capability of oxyradicals scavenging capacity and a lower functionality of phase II biotransformation mechanisms associated to glutathione S-transferase. Overall, the results suggest that M. pharensis has the capability to develop cellular and physiological adaptations to chemical-mediated stress, with yet unknown possible energy trade-offs to sustain stress response.